Carboniferous to Early Permian tectono-sedimentary evolution in the western Junggar Basin, NW China: implication for the evolution of Junggar Ocean - Yang, Fan; Li, Jianzhong; Lu, Shan; Bian, Baoli; Liu, Hailei; Wei, Yanzhao; Qi, Xuefeng; Yang, Hao (Frontiers in Earth Science, 2023)
The discovery of Carboniferous hydrocarbon source rocks in the Mahu-Shawan Sag has implied considerable exploration potential in the Carboniferous strata in the western Junggar Basin. However, controversy has long surrounded when and how the Junggar Ocean was eventually closed, leading to a poor understanding of the Carboniferous basin evolution and the continental growth of the Central Asian Orogenic Belt. We performed stratigraphic and geochronologic studies to establish the chronostratigraphic framework of the western Junggar Basin to better understand its tectonic-sedimentary evolution during the Carboniferous-Early Permian. Three tectonostratigraphic units in the southern West Junggar region have been identified as Early Carboniferous shallow-deep marine sequences, Late Carboniferous coast-shallow marine sequences, and Early Permian continental sequences. The Carboniferous strata are similar to forearc and backarc-rift sequences in the Western Fault Belt and the Mahu-Shawan Sag, respectively. The Lower Permian strata in the southern West Junggar region are all continental sequences. Seismic profiles indicate extensional settings in the early stage of Late Carboniferous and Early Permian but a compressional setting at the end of Late Carboniferous. Geochemical data have suggested a Carboniferous continental arc setting and an Early Permian within-plate extensional setting. Meanwhile, calc-alkaline arc magma migrated from the Zhongguai High to the Western Fault Belt at the end of the Late Carboniferous. Collectively, the tectonic-sedimentary evolution in the Carboniferous-Early Permian of the southern West Junggar region can be divided into three stages: 1) Early Carboniferous subduction, 2) Late Carboniferous slab roll-back, and 3) Early Permian intra-continental evolution stage. This model constrains the closure of the Junggar Ocean at the Late Carboniferous.